Resonances: tuning into the echoes of the ecological collective. (July 2020) - Widdop Quinton, Helen; Ward, Kumara; Ahearn, Marilyn; Carapeto, Teresa
Abstract: Drawing on posthumanist and new materialism theorising, we take the concept of resonance for an a/r/tographic 'walk' to know, be and do differently, to challenge human-centric separatist ways that have resulted in our current socioecological crises. Beginning with Ingold's knotty thinking, we identify the notion of resonance as a node for exploring and thinking about interactions in the world. Guided by Barad's proposition of entangling ethico-onto-epistemic ways, our a/r/tographic thought experiments find resonances that echo through bodies, through connections as nature, through deep-time and modern spaces to notice and attend to intraactions within the ecological collective. Through art-full, thought-full scholartistic enquiry, we explore diffractive encounters to consider resonance as a conceptual tool for tuning into and harmonising with the entanglements of body–mind–space–time–matter. We pose this exploration of resonance as the start of a knotty theory conversation for shifting into a new 'common world' knowing, being and doing.